Pola Aktivitas Informal Pada Ruang Terbuka di Kp3 Kota Lhokseumawe - Baihaqi, Baihaqi; Karsono, Bambang; Aiyub, Hendra (Rifa'Institute, 2023)
Jagu Beach Coastal Road is located at the end of Lhokseumawe city center, precisely in the Lhokseumawe Port Security Unit (KP3). Even though the place is not an Instagrammable place, many tourist hunters visit it. Apart from offering a beautiful panoramic view of the sea, along the coastline there are also dozens of traders serving various culinary delights on the Coastal Road of Jagu Beach, Lhokseumawe City, so that this is utilized by street vendors in their marketing strategies. Its main activities are strongly influenced by commercial activities, both formal and informal trade. The informal trade sector has both positive and negative impacts on the region. Street vendors occupy the pedestrian right up to the road shoulder which results in a shift in pedestrian activity space to the road shoulder plus a lack of adequate parking space, which has an impact in the form of a lack of circulation for vehicles passing through it. This research aims to determine activity patterns as well as the causes and utilization of road corridors dominated by street vendors and their positive impact on the livability and sustainability of the city of Lhokseumawe. A mixed methods research approach was applied in this research to analyze descriptive and qualitative data obtained through observation, mapping, documentation and interviews on the Jagu Coastal Road, Lhokseumawe City. The research results reveal that this phenomenon contributes to the continuity of urban life in the afternoon and evening and becomes a popular place for people to gather. This helps to attract a crowd that can contribute to the economic livelihood of the city. On the other hand, this place shows the high level of dependence on street vendors to support their income.